A retrospective evaluation of term infants treated with surfactant therapy - Özge Sürmeli-Onay (Journal of Pediatric and Neonatal Individualized Medicine, 2015)
Aim: To investigate the clinical and therapeutic characteristics and outcomes of term infants who received surfactant therapy (ST) for severe respiratory failure in our neonatal intensive care unit (NICU). Methods: The medical records of term infants (gestational age ≥ 370/7 weeks) who received ST between 2003-2012 in NICU of Hacettepe University Ihsan Dogramaci Children’s Hospital were evaluated retrospectively. Results: During ten years period, 32 term infants received ST; the mean gestational age was 38.1 ± 0.88 wk and the mean birth weight was 2,936 ± 665 g. The underlying lung diseases were severe congenital pneumonia (CP) in 13 (40.6%), acute respiratory distress syndrome (ARDS) in 5 (15.6%), meconium aspiration syndrome (MAS) in 5 (15.6%), congenital diaphragmatic hernia (CDH) in 4 (12.5%), respiratory distress syndrome in 3 (9.4%) and pulmonary hemorrhage in 2 (6.3%) infants. The median time of the first dose of ST was 7.75 (0.5-216) hours. Pulmonary hypertension accompanied the primary lung disease in 9 (28.1%) infants. Mortality rate was 25%. Conclusion: In term infants, CP, ARDS and MAS were the main causes of respiratory failure requiring ST. However, further prospective studies are needed for defining optimal strategies of ST in term infants with respiratory failure.